Evolution of Threshold Displacement Energy in Irradiated Graphite - Vukovic, F.; Leyssale, J.; Aurel, P.; Marks, Nigel (2018)
Molecular-dynamics simulations are used to compute the threshold displacement energy (Ed) in a series of progressively damaged graphite structures. The Ed values are obtained by a statistically robust probabilistic method using a large number of primary-knock-on-atom events at energies up to 100 eV. No sharp threshold for Ed is observed, and a number of possible definitions are considered. For pristine graphite, the best estimate of Ed is 24 eV. Ed decreases with increasing irradiation damage, dropping by nearly a factor of 2 at a dose of one displacement per atom. For a fully disordered amorphous-carbon structure, Ed is around 5 eV. This evolution of Ed is an important missing ingredient in current estimates of radiation doses in nuclear reactors, which assume Ed is constant over the reactor lifetime, despite substantial structural evolution.